Militantisme féministe et pouvoir politique : parcours de deux parlementaires féministes belges (1945-1960) - Catherine Jacques (Amnis)
If Belgian women were eligible at all levels of power as from 1920, however they had to wait until 1948 before being able to vote. During the inter-bellum, women eligibility remained symbolic: only six women sat in the Parliament. After the second World War, these somehow deceiving results were countered by the entrance within the Parliament of two notorious feminists who sat there for 15 years. Completely using their parliamentary initiative, they obtained in less than ten years a row of significant advances, which were un-hoped before the war, in the realm of women rights. Looking at these two career paths, the article examines the nature and meaning of this twin political and personal commitment. It also raises the question of networks, relationships and multiple go-betweens needed in a democratic society by a pressure group willing to see its programme coming true. The analysis of the political tactics and strategies used to reach these feminists goals is the backbone of this article.